Genomic methylation inhibits expression of Hepatitis B virus envelope protein in transgenic mice : a non-infectious mouse model to dtudy silencing of HBV surface antigen genes - Graumann, Franziska; Churin, Yuri; Tschuschner, Annette; Reifenberg, Kurt; Glebe, Dieter; Roderfeld, Martin; Roeb, Elke; Justus Liebig University Giessen (My University, 2015)
Objective:The Hepatitis B virus genome persists in the nucleus of virus infected hepatocytes where it serves as template for viral mRNA synthesis. Epigenetic modifications, including methylation of the CpG islands contribute to the regulation of viral gene expression. The present study investigates the effects of spontaneous age dependent loss of hepatitis B surface protein- (HBs) expression due to HBV-genome specific methylation as well as its proximate positive effects in HBs transgenic mice. Methods: Liver and serum of HBs transgenic mice aged 5 33 weeks were analyzed by Western blot, immunohistochemistry, serum analysis, PCR, and qRT-PCR. Results:From the third month of age hepatic loss of HBs was observed in 20% of transgenic mice. The size of HBs-free area and the relative number of animals with these effects increased with age and struck about 55% of animals aged 33 weeks. Loss of HBs-expression was strongly correlated with amelioration of serum parameters ALT and AST. In addition lower HBs-expression went on with decreased ER-stress. The loss of surface protein expression started on transcriptional level and appeared to be regulated epigenetically by DNA methylation. The amount of the HBs-expression correlated negatively with methylation of HBV DNA in the mouse genome. Conclusions: Our data suggest that methylation of specific CpG sites controls gene expression even in HBs-transgenic mice with truncated HBV genome. More important, the loss of HBs expression and intracellular aggregation ameliorated cell stress and liver integrity. Thus, targeted modulation of HBs expression may offer new therapeutic approaches. Furthermore, HBs-transgenic mice depict a non-infectious mouse model to study one possible mechanism of HBs gene silencing by hypermethylation.
Keywords: ddc:610